EXPLORING JAMES MCCROSKEY’S RESEARCH ON WILLINGNESS TO COMMUNICATE IN L1 CONTEXTS: IMPLICATIONS FOR LANGUAGE TEACHING AND LEARNING - Borasheva, Aybolgan (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
This article provides an overview of James McCroskey's research on willingness to communicate and its relationship to communication apprehension. Specifically, the article focuses on McCroskey's studies on willingness to communicate in L1 contexts, including his findings on the factors that influence this construct and its relationship to language proficiency. The article also outlines potential directions for future research. Overall, the article emphasizes the importance of understanding willingness to communicate in diverse linguistic and cultural contexts and its potential implications for language teaching and learning.